First Successful Cultivation of the Edible Mushroom Macrolepiota dolichaula in Thailand - Leela Maya Rizal (Science Faculty of Chiang Mai University, 2019)
The wild edible mushroom Macrolepiota dolichaula is widely consumed in China, India and northern Thailand as seasonal delicacies. Optimal cultural conditions, spawn production, cultivation parameters in compost and an outdoor method for inoculating spawn of M. dolichaula in orchard soils were investigated. Among the nine media tested, the optimum mycelial growth was observed in malt extract agar (MEA). This mushrrom can grow at a wide range of temperatures and pH values, although the optimum temperature and pH for the mycelial growth were 30ฐC and pH 7.0 respectively. Among the seven substrates tested, red sorghum was the best substrates for spawn production. Red sorghum spawn was fully colonized within 14 days following inoculation. The mushroom grew well in compost made of a pasteurized mixture of rice straw, rice bran, gypsum, calcium carbonate, urea and diammonium phosphate that was composted, using the outdoor method. After application of casing, basidiomes were obtained at 25ฐC and 92% relative humidity. Fructification took place at 41 days from spawning and yields from four flushes from four compost baskets were recorded. Basidiomes were also observed from the spawn inoculated sites in the orchard during the rainy season, ten months following spawn inoculation into the soil. This report provides valuable information concerning the possibility to cultivation M. dolichaula in compost and gardens or orchards soils in Thailand.